In Vitro Comparison of the Krackow and Locking Loop Suture Patterns for Tenorrhaphy of Flat Tendons - Montgomery, R. D.; Barnes, S. L.; Wenzel, J. G. W.; Milton, J. L.; Terry, G. C. (Veterinary and Comparative Orthopaedics and Traumatology, 1994)
Tenorrhaphy of 20 pairs of canine patellar tendons, was by a modification of the Krackow suture pattern on one of the pair and a single locking loop suture pattern on the contralateral tendon. The tenorrhaphies were pulled apart at a rate of 127 cm/min. The mode of failure for all tendons was disruption of the tendon and the suture material pulling out of the tendon. The mean maximum load for the locking loop suture pattern was 67.2 N (S.D. 7.8), compared to 61.3 N (S.D. 9.3) for the modified Krackow suture pattern. The mean energy absorbed to maximum load was 0.54 Joules (J) (S.D. 0.168) for the locking loop and 0.37 J (S.D. 0.12) for the modified Krackow. The mean stiffness was 4846 N/m (S.D. 803) for the locking loop and 5573 N/m (S.D. 921) for the modified Krackow.This study indicated the locking loop suture pattern was significantly better than the modified Krackow suture pattern in maximum strength (p = 0.03), total energy absorbed to failure (p = 0.0004) and stiffness (p = 0.004). Both suture patterns are suitable for use in flat tendons or ligaments based on their maximum strength. However, the effect of the modified Krackow suture pattern on vascularity and healing has not been evaluated.The locking loop suture pattern proved to be significantly better than the modified Krackow suture pattern in maximum strength, total energy absorbed to failure and stiffness.
Keywords: Krackow suture pattern; locking loop suture pattern; tenorrhaphy; flat tendons